2007
DOI: 10.1378/chest.06-2077
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pulmonary Embolism Is an Independent Predictor of Adverse Events in Severe Decompensated Heart Failure Patients

Abstract: Acute PE commonly complicates the hospital course of patients with severe CHF, increasing the length of hospital stay and the chance of death or rehospitalization at 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…However, the 36-month total and CV mortality for both studied groups was similar. It partly confirms the results of the Darze et al study [4], which showed a trend towards a higher 3-month mortality rate for patients with CHF with confirmed APE compared to patients with CHF. In that study, a combination of 3-month mortality with 3-month re-hospitalization showed a significant predominance of adverse events in patients with APE by 72.2% vs. 43.5%, respectively (p = 0.02) [4].…”
Section: Variablessupporting
confidence: 87%
See 3 more Smart Citations
“…However, the 36-month total and CV mortality for both studied groups was similar. It partly confirms the results of the Darze et al study [4], which showed a trend towards a higher 3-month mortality rate for patients with CHF with confirmed APE compared to patients with CHF. In that study, a combination of 3-month mortality with 3-month re-hospitalization showed a significant predominance of adverse events in patients with APE by 72.2% vs. 43.5%, respectively (p = 0.02) [4].…”
Section: Variablessupporting
confidence: 87%
“…It partly confirms the results of the Darze et al study [4], which showed a trend towards a higher 3-month mortality rate for patients with CHF with confirmed APE compared to patients with CHF. In that study, a combination of 3-month mortality with 3-month re-hospitalization showed a significant predominance of adverse events in patients with APE by 72.2% vs. 43.5%, respectively (p = 0.02) [4]. In our study, total and CV mortality was evaluated and demonstrated a significant difference in frequency against patients with confirmed APE in a 6-month observation.…”
Section: Variablessupporting
confidence: 87%
See 2 more Smart Citations
“…Acutely decompensated heart failure is a highly lethal condition, whose prognosis is even worse when the patient develops pulmonary embolism 2 . A recent study has shown that 9% of the patients admitted with heart failure develop pulmonary embolism during hospitalization, which has been called incidence 3 .…”
Section: Introductionmentioning
confidence: 99%